Learning While Producing Using Low Cost Technology Innovation: the Cost of Maize Mill in Uganda - Nahamya, Wilfred K.; Mukakanya, Abel M. (International Journal of Vocational Education and Training, 2014)
Quality education should prepare learners with competencies required in the world of work (WoW). Technical Vocational Education and Training (TVET) graduates are expected to be fully prepared with no need for re-training. he Ministry of Education and Sports made eforts to institute remedial measures to address the inadequacies in competencies exhibited by the college graduates. Among the reforms was transformation of curriculum to competence based training. herefore, this paradigm shit in curriculum requires engineering technicians to design, develop and implement stipulated real life projects aimed at learning while producing using available low cost means. his conceptual paper shares the views on the innovations in technology of fabricating a maize mill implemented by Mechanical Engineering TVET trainees in Uganda.